2021
DOI: 10.3389/fpsyg.2021.636520
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and Social Support: Examining Links With Psychological Wellbeing Among UK Students and Non-students

Abstract: The purpose of this multi-study article was to investigate the roles of adaptability and social support in predicting a variety of psychological outcomes. Data were collected from Year 12 college students (N = 73; Study 1), university students (N = 102; Study 2), and non-studying members of the general public (N = 141; Study 3). Findings showed that, beyond variance attributable to social support, adaptability made a significant independent contribution to psychological wellbeing (life satisfaction, psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 58 publications
10
56
1
Order By: Relevance
“…We can infer that the adjustments required by students to navigate these uncertain circumstances were well met by the psychological attribute of adaptability. This expands on the pre-COVID-19 evidence base for the positive effects of adaptability on students' educational outcomes (Martin et al, 2013;Holliman et al, 2018Holliman et al, , 2019Holliman et al, , 2021. Thus, in line with Collie et al (2020a); see also Collie and Martin, 2016), it seems that adaptability fosters mastery and efficacy experiences-manifested in our research by online learning self-efficacy.…”
Section: Findings Of Particular Notesupporting
confidence: 71%
See 1 more Smart Citation
“…We can infer that the adjustments required by students to navigate these uncertain circumstances were well met by the psychological attribute of adaptability. This expands on the pre-COVID-19 evidence base for the positive effects of adaptability on students' educational outcomes (Martin et al, 2013;Holliman et al, 2018Holliman et al, , 2019Holliman et al, , 2021. Thus, in line with Collie et al (2020a); see also Collie and Martin, 2016), it seems that adaptability fosters mastery and efficacy experiences-manifested in our research by online learning self-efficacy.…”
Section: Findings Of Particular Notesupporting
confidence: 71%
“…Adaptability is the capacity to regulate one's behaviors, thoughts, and feelings in response to novel, variable, uncertain, and unexpected situations and circumstances (Martin et al, 2012(Martin et al, , 2013. Adaptability has been identified as an important capacity for students' academic and personal development, including their motivation, engagement, achievement, and socialemotional wellbeing (Martin et al, 2013;Holliman et al, 2018Holliman et al, , 2019Holliman et al, , 2021. Given adaptability is specifically aimed at successfully navigating change, uncertainty, and novelty, it is also likely a vital personal attribute to support students during periods of novelty, variability, and uncertainty, such as with COVID-19 restrictions and lockdowns, including periods of online learning through these times.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptability is an essential academic and personal development capacity among students (8). The better the E-learning adaptability of students, the better the learning effect (9). Conversely, learning maladjustment may adversely affect their learning efficiency and the occupation prospects for development (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, social media provides several ways to interact both with close ties, such as family, friends, and relatives, and weak ties, including coworkers, acquaintances, and strangers (Chen and Li, 2017 ), and plays a key role among people of all ages as they exploit their sense of belonging in different communities (Roberts and David, 2020 ). Consequently, despite the fears regarding the possible negative impacts of social media usage on well-being, there is also an increasing number of studies highlighting social media as a new communication channel (Twenge and Campbell, 2019 ; Barbosa et al, 2020 ), stressing that it can play a crucial role in developing one's presence, identity, and reputation, thus facilitating social interaction, forming and maintaining relationships, and sharing ideas (Carlson et al, 2016 ), which consequently may be significantly correlated to social support (Chen and Li, 2017 ; Holliman et al, 2021 ). Interestingly, recent studies (e.g., David et al, 2018 ; Bano et al, 2019 ; Barbosa et al, 2020 ) have suggested that the impact of smartphone usage on psychological well-being depends on the time spent on each type of application and the activities that users engage in.…”
Section: Introductionmentioning
confidence: 99%